Challenges in the Commercialization of Lithium (Li)–Sulphur (S) Batteries † - Indra Neel Pulidindi; Varadarajan Thirukallam Kanthadai; Viswanathan Balasubramanian (International Journal of Advance in Molecular Engineering, 2024)
Li-S batteries can be used in drones owing to their high gravimetric energy density (2600 Wh/kg of sulphur) as well as the high theoretical specific capacity values (1674 mAh/g) values. Most of the ground breaking inventions in energy sources occurred during war time (1st September 1939-2nd September 1945), including the discovery of the famous nuclear fission process that lead to the origin of the little boy and the fat man. Such innovation is expected in battery technology surpassing that of the Israeli iron dome and the design of energy efficient and high precision drones. The use of battery technology in drones for application in war is upcoming as seen in Ukraine and Gaza by the invading disruptive forces. The current review article is aimed at developing the advanced and state of the art cathode materials based on S modified carbon materials leading to sustainability, safety and cost effectiveness. As we are currently in the war time, this research on the development of cathodes for Li-S batteries is highly relevant for defence as well as for mobile and transportation application in the war zones.
Keywords: Carbon-sulphur composites; Cathodes; Cycling stability safety; Gravimetric energy density; Kinetics; Polysulfide intermediates; Rate capability; Shuttle effect; Specific capacity